The influence of Conservation Agriculture on soil biophysical properties, crop growth and yield in the UK - O'Sullivan, Bethany (2025)
The global intensification of agricultural land use has been driven by the need to maximise crop yields, often through practices such as tillage and the application of agro-chemicals. However, this intensification has revealed significant challenges in maintaining long-term soil structure and function. The actions of common soil cultivation practices can physically disrupt key soil properties, leading to diminished biological activity, the breakdown of soil aggregates, and the depletion of key organic carbon compounds. Consequently, conventionally managed soils are subject to erosion rates that are 1–2 orders of magnitude higher than natural soil formation rates. In response to these challenges, Conservation Agriculture (CA) is seen as a sustainable farming approach aimed at improving soil structure, enhancing soil function, and reducing the labour and fuel demands associated with conventional soil management. The principles of CA—minimal soil disturbance, permanent soil cover, and crop rotation—have shown promise in enhancing soil water use efficiency in arid and semi-arid regions. However, the effects on the final yield of CA techniques have been seen to be highly variable and heavily dependent on crop type, aridity, climate, and time. In the UK, CA practices have, in some cases, been found to be effective and profitable, but the causes of profit losses in others. Additionally, there are few studies that have attempted to link the changes CA practices cause in the soil to differences in the final yield. This thesis investigates the long-term effects of CA practices, including zero tillage, reduced tillage, and mouldboard ploughing followed by rolling, both with and without crop residue retention, on the physical, biological, and chemical properties of soil. The trial site was conducted as a long-term (c. 7-9 years) trial at the University of Nottingham, England, and supplemented by field samples from long-term zero tillage farms. Traditional soil assessment methods were used alongside advanced X-ray Computed Tomography (CT) to evaluate soil structure, function, and pore arrangement. The first experimental chapter examines the effects of CA practices on soil physical, biological, and chemical properties approximately 7–10 years after their adoption. Initial results showed that zero tillage led to an increase in soil bulk density; however, after nine years of CA management, the bulk density in zero tillage plots decreased to 0.991 g cm-3, compared to 1.03 and 1.04 g cm-3 under minimum tillage and ploughing, respectively. This reduction in bulk density was associated with increases in soil organic carbon, earthworm activity, and soil moisture content. Additionally, reduced tillage systems, including both zero and minimum tillage, exhibited higher soil organic matter, soil organic carbon content, and microbial biomass. These findings suggest that the benefits of CA practices in the UK become more pronounced over time, with key improvements in soil health being most evident from 8-9 years post-adoption. The subsequent chapter explored the impact of these soil changes on crop growth and yield. While crop establishment rates were consistently lower under reduced tillage systems, these differences did not result in consistent, significant yield disparities over the course of the trial, which began in 2014. Notably, the effects of tillage practices varied by crop species. For instance, wheat was able to compensate for reduced establishment rates through tillering, whereas faba beans showed a significant yield reduction under zero tillage, likely due to a lower capacity to compensate for poor initial establishment. Despite these variations, the average yields in zero and minimum tillage plots since establishment of the trial in 2014 were not significantly different from those in ploughed plots, whilst benefitting from the lower input requirements associated with CA practices. To investigate the hypothesis that poor crop establishment under zero tillage is caused by suboptimal seed-soil contact, X-ray CT was employed to image seeds and the surrounding soil after drilling. It was revealed that zero tillage seedbeds exhibited a similar porosity to ploughed seedbeds (17% versus 18%), while minimum tillage seedbeds had a significantly higher average porosity (22%). The minimum tillage plots also displayed significantly larger macropores (770 mm3) than either the zero tillage (200 mm3) or ploughed plots (220 mm3). However, despite lower average porosities and smaller macropores which are usually associated with increased seed-soil contact, the seed-soil contact of the zero tillage (78%) and ploughed plots (70%), were significantly lower than the minimum tillage plots (82%). The increased seed-soil contact in minimum tillage plots may be attributed to a deeper sowing depth and resulting compression of the soil around the seeds. However, seed-soil contact did not correlate with crop establishment rates, suggesting that other factors may contribute to the reduced establishment observed under zero tillage. An additional experiment utilising the zero tillage and ploughed plots in the trial alongside samples from long-term (c. 20 year) zero tillage fields in practise in the UK, focused on the stocks, distribution, and lability of soil carbon. X-ray CT scans revealed that zero tillage soils had larger and deeper macropores, with pore networks extending twice as far into the soil as those in ploughed soils. This consolidation of pore space into larger, deeper pores is theorised to provide physical protection to organic matter in the soil from decomposition by soil biota such as earthworms and microbes. Consequently, significantly higher total soil organic carbon stocks were observed in all sites under zero tillage longer than five years, and all zero tillage sites regardless of age saw higher soil organic carbon stocks at the soil surface. Additionally, Rock-eval (6) analysis was conducted to investigate the stability of the carbon stocks present in the soil. It was found that there was an increase in both labile and recalcitrant carbon pools under zero tillage, but of labile carbon to a greater degree, suggesting enhanced physical protection of organic carbon. The data from this study underscores the potential long-term benefits of Conservation Agriculture in temperate climates, particularly in terms of soil health, carbon storage, and reduced input requirements. While initial challenges such as lower crop establishment rates under reduced tillage were observed, these were offset by significant improvements in soil structure, function, and carbon sequestration over time. Over nine years of study, while some years saw significant differences in yield, there were no overall trends, and no tillage system performed best. The study highlights the importance of sustained commitment to CA practices to fully realise their benefits, demonstrating that long-term adoption of CA can lead to enhanced agricultural productivity and sustainability.